Studi Keberhasilan Ibu Pekerja Dalam Memberikan Asi Eksklusif - Wa Ode Nurul Mutia (Jurnal Ilmu Kebidanan, 2023)
Background: Success in providing exclusive breastfeeding as a working mother needs to have a lactation management attitude so as to avoid environmental obstacles. Giving complementary food intake of breast milk or formula milk too early will cause risks to the baby such as digestive disorders, obesity and diarrhea. The lack of skills and the presence of obstacles that a working mother cannot anticipate will disrupt breastfeeding and work activities. Purpose: to find out the success study of working mothers in providing exclusive breast milk in the working area of the Meo-Meo Health Center. Method: used in this research is quantitative research, with the approach of distributing questionnaires and analyzed using univariate by looking at the appearance of the frequency distribution. Results: The majority of successful working mothers in providing exclusive breastfeeding have a positive attitude. Then the majority of successful working mothers in providing Exclusive Breastfeeding have supportive husbands and the majority of successful working mothers in providing Exclusive Breastfeeding have good knowledge. Suggestion: health workers are expected to carry out routine activities regarding counseling education for working mothers by using media aids or visual aids to make it easier for working mothers to understand the procedures for implementing breast milk so that they can determine attitudes in making decisions.